LAVENDER AROMATHERAPY ON REDUCING ANXIETY IN PATIENTS WITH RECURRING DIABETIC FOOT WOUNDS: A PRE-EXPERIMENTAL STUDY - Hanafi Hanafi; Ainun Najib Febrya Rahman; Ledy Ervita (CV. Fahr Publishing, 2026)
The prevalence of diabetic foot ulcers is currently quite high worldwide, with 6.3% of diabetic patients experiencing them. In Southeast Asia, the prevalence of diabetic foot ulcers reaches 5.5% of the total number of diabetes mellitus sufferers. Sudden changes in the condition can cause diabetic foot ulcer sufferers to exhibit several negative psychological reactions, such as anger, feelings of worthlessness, increased anxiety, and stress. Find out if lavender aromatherapy helps patients with diabetic foot ulcers at the Kitamura Clinic in Pontianak feel less anxious. The study's participants were divided into two groups: an intervention group and a control group, using a pre-experimental design. Over the course of six months, all 77 patients with diabetes mellitus and foot ulcers.Results: Because the data were not normally distributed, a bivariate analysis was performed in SPSS using the Wilcoxon test. Lavender aromatherapy affected anxiety levels in patients with diabetic foot ulcers, as evidenced by the intervention group's p-value of 0.000 (< 0.05), which demonstrated a significant difference between pre- and post-intervention assessments. On the other hand, the group that received H2O aromatherapy had a p-value of 0.158 (> 0.05), indicating no significant change between pre- and post-intervention assessments and that H2O aromatherapy did not affect anxiety levels in patients with diabetic foot ulcers. Patients who received lavender aromatherapy saw a higher and statistically significant decrease in anxiety levels after the intervention as compared to the control group. These results validate lavender aromatherapy's efficacy as a supplemental intervention for lowering anxiety in diabetic foot ulcer patients.